Long-range interaction between dust grains in plasma - Mishagli, D.Yu. (Condensed Matter Physics, 2014)
The nature of long-range interactions between dust grains in plasma is discussed. The dust grain interaction potential within a cell model of dusty plasma is introduced. The attractive part of inter-grain potential is described by multipole interaction between two electro-neutral cells. This allowed us to draw an analogy with molecular liquids where attraction between molecules is determined by dispersion forces. Also main ideas of the fluctuation theory for electrostatic field in cell model are formulated, and the dominating contribution to attractive part of inter-grain potential is obtained.